Antimicrobial Resistant Coagulase-Negative Staphylococci Carried by House Flies (Musca domestica) Captured in Swine and Poultry Farms - Fabrizio Bertelloni; Giulia Cagnoli; Flavio Bresciani; Bruno Scotti; Luca Lazzerini; Marco Marcucci; Giuseppe Colombani; Valentina Virginia Ebani (MDPI AG, 2023)
House flies (Musca domestica) are very diffuse insects attracted by biological materials. They are abundantly present in farm environments and can frequently come in contact with animals, feed, manure, waste, surfaces, and fomites; consequently, these insects could be contaminated, carry, and disperse several microorganisms. The aim of this work was to evaluate the presence of antimicrobial-resistant staphylococci in house flies collected in poultry and swine farms. Thirty-five traps were placed in twenty-two farms; from each trap, 3 different kinds of samples were tested: attractant material present in the traps, the body surface of house flies and the body content of house flies. Staphylococci were detected in 72.72% of farms, 65.71% of traps and 43.81% of samples. Only coagulase-negative staphylococci (CoNS) were isolated, and 49 isolates were subjected to an antimicrobial susceptibility test. Most of the isolates were resistant to amikacin (65.31%), ampicillin (46.94%), rifampicin (44.90%), tetracycline (40.82%) and cefoxitin (40.82%). Minimum Inhibitory concentration assay allowed to confirm 11/49 (22.45%) staphylococci as methicillin-resistant; 4 of them (36.36%) carried the mecA gene. Furthermore, 53.06% of the isolates were classified as multidrug-resistant (MDR). Higher levels of resistance and multidrug resistance were detected in CoNS isolated from flies collected in poultry farms than in swine farms. Therefore, house flies could carry MDR and methicillin-resistant staphylococci, representing a possible source of infection for animals and humans.